The impact of imputed rent on old-aged poverty: The evidence for the Luxembourg Income Study - Edyta Marcinkiewicz; Filip Chybalski (Luxembourg Income Study (LIS), 2023)
Our study contributes to the discussion on the impact of imputed rent on poverty. In this paper, we address the issue of the relevance of imputed rent specifically in regard to the welfare of older people. Our aim is to assess how imputed rental income relates to monetary income for both homeowners and subsidized tenants, to draw more comprehensive picture of poverty among retirees, who are considered to be an economically vulnerable group. We employ the Luxembourg Income Study database (wave X) to compare the situation of elderly households in seventeen countries in this respect. The results obtained demonstrate that although imputed rental income is quite universal among the older population, there is a lot of a cross-country variation in this respect, which partly can be attributed to the methodological constraints. Nonetheless, we can conclude that imputed rental income contributes to poverty reduction. This also entails some policy implications in the long run, especially in the face of housing market shifts, rising wealth inequalities and the expected reduction in the generosity of public pensions.
Keywords: 330; imputed rent; housing; poverty; elderly households